Pengaruh Hospitality Pendekatan Soft Skill Karyawan Terhadap Peningkatan Kualitas Pelayanan Hotel di Kota Makassar dan Pare-Pare, Sulawesi Selatan - Hamsiati, Hamsiati (Politeknik Pariwisata NHI Bandung, 2020)
This study aims to analyze the relationship of employee hospitality with soft skills in intrapersonal, intrapersonal, attitudes and behaviors related to improving the quality of hotel services in Makassar City and Parepare; and analyze the application of hospitality with gentle expertise, which is dominant in improving the quality of hotel services in the cities of Makassar and Parepare. This research is a quantitative descriptive study describing factual conditions with data collected from questionnaires through a direct collection of objects and interviews. The study population was hotel employees in the Food and Beverage Service (F&B) section, and a sample of 38 respondents based on purposive sampling techniques. Descriptive data analysis through frequency and percentage, and statistical analysis using Multiple Linear Regression. The findings of this study are the hospitality of employees with intrapersonal, interpersonal, soft skills and attitudes that have been applied by employees and have a positive and significant influence both simultaneously and partially on improving the quality of hotel services in Makassar City and Parepare. The results of the analysis also showed that all variables collected consisted of intrapersonal, interpersonal, attitudes and significant behaviors based on the value of tcount> ttable, and were found to be related to the hospitality obtained by soft skills consisting of attitudes (X3) which were dominant in Makassar and Parepare. A value of 0.862, which shows the same way as a hotel, is hospitality that refers to soft skills, which determine the quality of hotel services in Makassar City and Parepare.